THE EFFECTIVENESS OF TEACHING GRECO-ROMAN WRESTLING TEENAGERS IN ATTACK TECHNIQUES - Karimov Fakhriddin Hurramovich; Tashkent Financial Institute; Isakav Jamshid Zikrillayevich (International Journal of Innovations in Engineering Research and Technology, 2021)
Greco-Roman wrestling is an ancient sport, now highly developed, the first of its kind to be included in the program of the modern Olympic Games (1896), many scientific studies are conducted by scientists, but the direction of this work is not always the same.